Coffin production / Jack Danautoba Sumatra ... [et al.] - Sumatra, Jack Danautoba; Jeffrey, Aerron; Amat, Halimatu Saadiah; Halid, Zuhana; Benedict Jipiu, Gesmaire (2009)
We choose coffin product in our business because it is the needs of natural life. Our group consists of four members that basically have experience in doing business. Everyday people die and coffin is one of the necessary things that most of people in Sabah will use one day. The idea to choose coffin as our main product comes after making some of observation and research the potential that we have in Sabah especially around Kota Kinabalu. This business is profitable because the high demand and low production and because of the material and the process makes the price of one coffin can reach more than RM10,000 per unit. Our business plan is about being one of the producers of coffin in Sabah that offer the most cheaply and affordable price to everyone. Even though there another factory that produce coffin but it can be counted and it's rare to see and the number of bumiputra coffin maker is less. What makes our business more attractive is we are not only making coffin with the lowest price but also our priority to put a high and best quality on our product. We are not only making coffin for the Christian but also to other religion by supply in our range of product.